Incorporation of Lokon Ash, Plastic and Fish Scales Waste in Concrete Composites and Their Compressive Strength - Maria Daurina Bobanto; Dolfie Paulus Pandara; Maureen Kumaunang; Gerald Hendrik Tamuntuan; Ferdy Ferdy; Riskivany Marsaoly (Sam Ratulangi University, 2025)
Sustainable construction efforts to reduce carbon dioxide emissions from cement production suggest incorporating pozzolanic and waste materials into concrete composites. This research focuses on evaluating the compressive strength of concrete composites that include Mount Lokon volcanic ash, plastic waste, and fish scale waste. The study was conducted through several stages: preparation of raw materials, production of concrete composites with varying mix ratios, curing for 14–28 days, and compressive strength testing using a Compression Testing Machine (CTM). The findings indicate that replacing 7% of cement with Lokon ash provides the best compressive strength, reaching 2.7 MPa after 14 days of curing. When plastic is used as an aggregate at 13% in a mix of 13% cement, 7% Lokon ash, and 67% sand, the compressive strength improves to 3.7 MPa after 28 days of curing. The inclusion of 7% fish scale waste in the composite increases compressive strength, though it still falls short of the minimum strength required by SNI standards. Lokon ash, plastic, and fish scale waste have potential for use in non-structural concrete blocks. Further research is required to better understand the role of fish scale waste as a filler in concrete blends with cement, Lokon ash, plastic, and sand. The integration of these materials supports the advancement of sustainable construction practices.